4(5x+1)+4(x-3)=

Simple and best practice solution for 4(5x+1)+4(x-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(5x+1)+4(x-3)= equation:


Simplifying
4(5x + 1) + 4(x + -3) = 0

Reorder the terms:
4(1 + 5x) + 4(x + -3) = 0
(1 * 4 + 5x * 4) + 4(x + -3) = 0
(4 + 20x) + 4(x + -3) = 0

Reorder the terms:
4 + 20x + 4(-3 + x) = 0
4 + 20x + (-3 * 4 + x * 4) = 0
4 + 20x + (-12 + 4x) = 0

Reorder the terms:
4 + -12 + 20x + 4x = 0

Combine like terms: 4 + -12 = -8
-8 + 20x + 4x = 0

Combine like terms: 20x + 4x = 24x
-8 + 24x = 0

Solving
-8 + 24x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 24x = 0 + 8

Combine like terms: -8 + 8 = 0
0 + 24x = 0 + 8
24x = 0 + 8

Combine like terms: 0 + 8 = 8
24x = 8

Divide each side by '24'.
x = 0.3333333333

Simplifying
x = 0.3333333333

See similar equations:

| 11x-19y=-7 | | 7y-21=-8y | | 4x=3+10 | | 2(x+3)=18-6x | | v^3+8=0 | | 90x-1.5x^2=1200000 | | 2.2x+0.4=2(1.1x-0.1) | | 14x+6+10x+6=180 | | 7y+21=-8y | | 25x^2-95x+61=0 | | 2+7x=20x | | 3x-3*x-3=2x-1*2x-1*2x | | -5x-(6x-3)=-8x+27 | | -t+47282=4848235 | | -8(1-7n)-1=-9+8n | | 7x-15=11+5x | | -10c=-40 | | 7x+9x=20 | | -42x-6=42x+7+6 | | 3/7=p-1/7 | | 60a^3b-52a^2b+8ab= | | 9x+8=6x+7 | | 10-10x=23-17 | | 16x^2+40x+16=-9 | | 7=3(-6x+7) | | 3k+8=17 | | x^2+9x+10= | | 8(x+6)-4= | | R-24=-14 | | t(3t-2)=0 | | (-75)=25 | | 4x(2)=16 |

Equations solver categories